ANALISIS DAMPAK BRAND LOYALTY, BRAND AWARENESS, PERCEIVED QUALITY DAN BRAND ASSOCIATION TERHADAP CUSTOMER VALUE PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN TULUNGAGUNG - Subagiyo, Rokhmat; Adlan, M. Aqim (An-Nisbah: Jurnal Ekonomi Syariah, 2018)
Abstract: The beginning of this research comes from the variable of brand loyalty, brand awareness, quality impression and brand association is expected to increase customer value. This is because the view of universities is a very broad discussion in order to be a contribution for students to feel satisfied with the services provided. The purpose of this study is to examine: the impact of Brand Loyalty, Brand Awareness, Quality Perceptions, and Brand Associations on Customer Value to students of the Faculty of Economics and Islamic Business IAIN Tulungagung. The research method used in this research is quantitative type eksplanotry research, with the type of causality relationship on the variables through hypothesis testing. The sample selection technique is done by using non probabality sampling method. Samples taken by students majoring in Sharia Economics, Islamic Banking, Syariah Accounting and Zakat Management and Endowments amounted to 359 respondents based on Slovin calculations. The analysis technique used is multiple linear regression analysis with SPSS program version 21. The result shows that brand loyalty, brand awareness, quality perception, brand associationÂ either partially or simultaneously have a significant impact on customer value.